Photorefractive keratectomy with extended ablation zone for recurrent corneal erosion syndrome accompanied with refractive errors: a study of effectiveness, safety, and refractive outcomes - Yu, Xinxin; Wang, Chenchen; Zhang, Zuhui; Zhang, Wuqi; Yang, Yizeng; Wu, Shuangqing (Frontiers in Medicine, 2025)
IntroductionThis retrospective study evaluated the effectiveness, safety and refractive outcomes of phototherapeutic keratectomy (PRK) with extended ablation zone in patients with recurrent corneal erosion syndrome (RCES) accompanied with refractive errors. Trans-epithelial photorefractive keratectomy (TPRK) for the contralateral eyes and phototherapeutic keratectomy (PTK) for RCES patients without refractive errors were included for comparison.MethodsThe study enrolled a total of 79 eyes from 62 patients, comprising 16 eyes (16 patients) in the PRK group, 11 contralateral eyes (11 patients) in the TPRK group, and 52 eyes (49 patients) in the PTK group. The demographic and clinical profiles of the participants were meticulously documented. Surgical parameters, such as the optical zone diameter, treatment zone diameter, and ablation depth, were recorded. Postoperative duration of corneal epithelialization, recurrence of corneal epithelial erosion, complications, visual acuity and refractive error were also recorded.ResultsThere was no significant difference of the treatment zone diameter between the PRK group (8.92 ± 0.57 mm) and the PTK group (9.15 ± 0.48 mm), while it was significantly larger in the PTK group than that in the TPRK group (8.55 ± 0.51 mm) (p = 0.001). In the PRK group, recurrence of epithelial erosion occurred in one eye after PRK, which was managed conservatively. Recurrence was found in three eyes after PTK, and two eyes resolved after corneal epithelium removal followed by the application of a bandage contact lens, while one eye resolved after retreated with PTK. In terms of refractive outcomes, the deviation of target spherical equivalent at the final visit was −0.25 ± 0.57 D and −0.13 ± 0.26 D in the PRK and TPRK groups, respectively, and all patients in both groups achieved an uncorrected visual acuity of 1.0 or better. In the PTK group, 76.5%, 82.1%, and 100% of patients achieved visual acuity equal to or better than preoperative levels at 1 week, 1 month and 3 months postoperatively. The change in spherical equivalent at the last visit was +0.09 ± 0.62 D. Delayed corneal epithelial healing occurred in two eyes (12.50%) in the PRK group, one eye (9.09%) in the TPRK group and eight eyes (15.38%) in the PTK group, which correlated with the formation of no-visual interfering corneal nebula and haze. Specifically, mild corneal nebula was found in one eye in the PTK group and one eye in the PRK group due to 30 to 60 days of corneal epithelialization. Temporal haze was observed in two eyes (12.50%) in the PRK group, and two eyes (18.18%) in the TPRK group, and one eye (1.92%) in the PTK group.ConclusionIn conclusion, the effectiveness and safety of PRK with extended oblation zone were comparable with PTK for RCES and the refractive outcomes were similar with TPRK. It is recommended for RCES patients accompanied with refractive errors for relieving symptoms and acquiring encouraging visual acuity simultaneously.